Blocking soluble TNFα sensitizes HER2-positive breast cancer to trastuzumab through MUC4 downregulation and subverts immunosuppression - Bruni, Sofia (2022)
Trastuzumab resistance is an important clinical issue. Although a plethora of resistance mechanisms have been characterized, few have been shown to be actionable. We have demonstrated that soluble TNFα isoform (sTNFα) upregulates mucin 4 (MUC4) expression, which shields the trastuzumab epitope on HER2, hindering its therapeutic effect in vitro and in vivo [1,2].